Profitability, Corporate Governance, and Family Ownership Effect on Corporate Social Responsibility Disclosure - I Made Gde Kamal Mulia; I Ketut Jati; Ni Luh Sari Widhiyani; Eka Ardhani Sisdyani (KRISNA: Kumpulan Riset Akuntansi, 2025)
The aim of this research is to analyze the effect of profitability, corporate governance, and family ownershipon corporate social responsibility disclosure. This research was conducted on manufacturing sectorcompanies listed on the Indonesia Stock Exchange with the observation year 2021 - 2023. The sample for thisresearch is family companies (Family Business Enterprise) which are included in the manufacturing industrygroup. The sampling method used was the purposive sampling method. This research uses secondary dataobtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and the company'sofficial website. The data collection method used in this research is the non-participant observation method.The data analysis technique used is multiple linear regression analysis. The findings show that profitability,corporate governance, and family ownership have a positive effect on corporate social responsibilitydisclosure.